Comprehensive Analysis of Insulator Performance in High Voltage Transmission Systems: Implications for Efficient Power Transfer - Ahsan, Matiullah; Bahrom, Md Nor Ramdon; Zainal, Zainab; Mohd Ariffin, Azrul; Muhammad Saufi, Muhammad Saufi; Mohd Yousof, Mohd Fairouz; Zambri, Nor Aira; Mustafa, Farahiyah; Mohd Noh, Faridah Hanim; Ab Ghafar, Aimi Syammi; Ahmed, Mehmood (semarak ilmu, 2024)
This research article examines the performance of insulators in high-voltage transmission systems, specifically focusing on their role in facilitating efficient power transfer along transmission lines. The study evaluates different types of insulators used in various geographical regions and assesses their withstand voltage characteristics. The research demonstrates that glass insulators outperform plastic and ceramic insulators in terms of electric field behavior. The study also investigates the behavior of AC-energized insulators in polluted and non-polluted conditions, providing insights for improving HVAC insulation design in polluted environments. The research recommends further experiments to examine insulator behavior under different applied voltage scenarios. Overall, the study emphasizes the importance of insulators in high-voltage transmission systems and provides valuable insights for developing advanced insulator technologies to enhance power transfer efficiency.